KINERJA KEUANGAN SEBELUM DAN SETELAH PEMEKARAN DAERAH - Putra, Benta Palantama (JURNAL FAIRNESS, 2019)
This study aimed to analyze the financial performance of the district or the city before and after the expansion in South Sumatera. The population in this study is the entire district of South Sumatera. This type of research used in this research is a quantitative descriptive. The sampling technique used was purposive sample and selected 6 parent districts that experienced split area. Data analysis tools in this test using analysis of the ratio, descriptive statistics, data normality test, and t test (paired t-test).The results of this research show that there are differences in financial performance of district governments before and after expantion in South Sumatera Province measured from the ratio of fiscal decentralization due to Total Income Original Area has increased after expantion, there are differences in financial performance of district governments before and after expantion in South Sumatra Province is measured from the ratio of capital expenditure compatibility due to capital expenditure (development) has increased after expantion, there is no difference in financial performance of district government before and after expantion in South Sumatera Province is measured from the ratio of Income Original Area growth due to the Income Original Area not changed, there was no difference in financial performance of district government before and after expantion in South Sumatera Province measured from ratio of regional finance dependence due to transfer revenue with total fund the regional apparatus did not change.